The Immunity-Infection Arms Race: An Islamic Philosophical and Educational Perspectives - Hanish, Irwan (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
This article explores the interdisciplinary nexus between the Islamic philosophy of science and immunology, explicitly focusing on the immunity-infection arms race. Using COVID-19 as a case study, the paper elucidates the complex interplay between the immune system and pathogens, serving as a primer for Islamic scholars and non-scientists. It pioneers the Islamic philosophical perspectives into the understanding of this arms race, arguing that Islamic teachings not only align with but also enrich the ethical dimensions inherent in immunological studies. The article further delves into the educational applications of Islamic perspectives, advocating for a multidisciplinary approach that synergizes scientific rigor with Islamic ethical considerations. Methodologically, the article employs logical, theological, and philosophical analyses of extensive scientific and religious literature. The study offers a robust framework congruent with scientific and Islamic principles. The article holds practical significance beyond academic discourse by: (1) fostering potential collaboration among Islamic scholars, scientists, and educators, and (2) contributing to global health initiatives, particularly in Muslim-majority countries. Overall, it serves as a novel contribution to the interdisciplinary dialogue, revolutionizing the education of science and Islam related to the health and well-being of the Muslim community.